Extradition As International Cooperation In International Crime Handling - Saroinsong, Sam Julius Richard (International Journal of Engineering and Technology, 2018)
Criminals from a country can avoid the reach of the law of their country by fleeing to other countries this is possible because of technological advances, especially transportation and communication, which in the end crime can become international. In general, every country in the world asserts that national law is inherent and reaches out to every citizen wherever he is, this is so that the person who commits a crime cannot be separated from the legal responsibility attached to him. However, the use of state power over citizens who are in the territory of another country cannot be implemented because it is hindered by the limited jurisdiction owned by the country. State jurisdiction is limited and limited by international law so that in handling criminals who escape to other countries having jurisdiction and legal authority having difficulty in prosecuting and punishing such criminals, and the necessary steps are to conduct international cooperation. In this literature study, the most appropriate method for tackling international crime was examined and from the study it was found that extradition agreements are effective and effective means of handling international crimes..